Experimental and Numerical Analysis of Crack Propagation in Light Composite Materials under Dynamic Fracturing - Petru, Michal; Broncek, Jozef; Lepsik, Petr; Novak, Ondrej (Communications - Scientific letters of the University of Zilina, 2014)
Research and analysis of mechanical properties including crack propagation in a light composite material is currently very important because composite structures are gradually becoming an alternative material that allows a significant reduction in the weight of car parts. This leads to an increase in efficiency in transport vehicles. This article describes experimental as well as model analysis of damage to composite textiles during dynamic fracturing. The obtained information provides an approach to the complex problem of crack propagation in composite textiles intended for use in car seats. This is especially important from the point of view of safety, because during an accident a significant overload of the human body occurs and its kinetic energy can cause deformation of a breach in the composite textile. Therefore, identifying the direction of crack propagation is very important for the safety of passengers. Experimental studies have demonstrated that a dynamic breach is caused by the significant deformation of the tested sample. The distribution and direction of crack propagation in the sample was studied using a FEM model, based on the Griffith-Irwin criterion with nonlinear orthotropic properties of the composite textile.